Recovery rates of selected body odor substances in different textiles applying various work-up and storage conditions measured by gas chromatography-mass spectrometry - Alves Soares, Tatjana; Owsienko, Diana; Härtl, Tobias; Loos, Helene (Analytica Chimica Acta, 2023)
Background: Body odor is an important aspect in interpersonal communication. For psychological and chemical research on body odors, suitable procedures for sampling and application, and analysis of body odors are essential. In this study, different textile fabrics (polyester, cotton, and Gazin gauze) were comparatively evaluated in view of their potential suitability for body odor sampling by determining recovery rates of selected body odor substances. In addition, the impact of sample preparation and storage conditions on the recovery rates was determined. Results: The recovery rates of dimethyl disulfide, (E)-non-2-enal, 5α-androst-16-en-3-one, 6-methylhept-5-en-2-one, heptanal and 3-sulfanylhexan-1-ol were determined under different conditions of storage (storage for 30 min at room temperature or storage for 30 min at room temperature followed by freezing at – 80 °C for 4 weeks) and sample work-up (solvent extraction with and without solvent-assisted flavour evaporation, in the following: SAFE). SAFE led to overall lower recovery rates with a significant effect for (E)-non-2-enal and 5α-androst-16-en-3-one. Nevertheless, the results showed that SAFE can be an essential step when working with a complex matrix. When comparing the different fabrics, except for (E)-non-2-enal no difference between the recovery rates obtained for cotton and polyester became evident. Gazin gauze showed lower recovery rates for all compounds. Finally, our results showed that the here investigated target compounds are stable during storage for four weeks at – 80 °C. Significance and Novelty: The results show on the one hand that the here investigated compounds were stable during storage and that the fiber type had limited influence on overall recovery rates. On the other hand, they highlight the limitations of using textile materials for sampling of volatile substances, especially with regard to low recovery rates for certain substances and the necessity of material pre-treatment or distillation steps for enabling GC-MS analysis after solvent extraction.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Adsorption; Cotton; Gazin gauze; Polyester; Release; Storage stability